Cooled radiofrequency denervation for treatment of sacroiliac joint pain: two-year results from 20 cases - Ho, Kok-Yuen; Mohamed, Abdul Hadi; Pasutharnchat, Koravee; Tan, Kian-Hian (Dovepress, 2013)
Sacroiliac joint pain is a common cause of chronic low back pain. Different techniques for radiofrequency denervation of the sacroiliac joint have been used to treat this condition. However, results have been inconsistent because the variable sensory supply to the sacroiliac joint is difficult to disrupt completely using conventional radiofrequency. Cooled radiofrequency is a novel technique that uses internally cooled radiofrequency probes to enlarge lesion size, thereby increasing the chance of completely denervating the sacroiliac joint. The objective of this study was to evaluate the efficacy of cooled radiofrequency denervation using the SInergy™ cooled radiofrequency system for sacroiliac joint pain.